Bioactivity of pyridine-2-thiolato-1-oxide metal complexes: Bi(III), Fe(III) and Ga(III) complexes as potent anti-Mycobacterium tuberculosis prospective agents - Machado, Ignacio Raúl (2014)
In the search for new therapeutic tools against tuberculosis and to further address the therapeutic potential of pyridine-2-thiol 1-oxide (Hmpo) metal complexes, two new octahedral [M(III)(mpo)3] complexes, with M = Ga or Bi, were synthesized and characterized in the solid state and in solution. Attempts to crystallize [Ga(III)(mpo)3] in CH2Cl2 led to single crystals of the reaction product [GaCl(mpo)2], where the gallium(III) ion is in a square basis pyramidal environment, trans-coordinated at the basis to two pyridine-2-thiolato 1-oxide anions acting as bidentate ligands through their oxygen and sulfur atoms. The biological activity of the new [M(III)(mpo)3] complexes together with that of the previously reported Fe(III) analogous compound and the pyridine-2-thiol 1-oxide sodium salt (Na mpo) was evaluated on Mycobacterium tuberculosis. The compounds showed excellent activity, both in the standard strain H37Rv ATCC 27294 (pan-susceptible) and in five clinical isolates that are resistant to the standard first-line anti-tuberculosis drugs isoniazid and rifampicin. These pyridine-2-thiol 1-oxide derivatives are promising compounds for the treatment of resistant tuberculosis.